(3GdYbjOI GdSdajI hGdQO Ydi GdefMQajf YfgG (B/s - (3GdLcfj, GdWjH Hf YeQ Hf GdMSjfs ((3HjQhJ (B- (3dHfGf (B:s (3GdecJH GdESdGej ,s (3OGQ GHf MRe ddWHGYI hGdfTQ hGdJhRjY ,s, 1999)
(3bO hVM ajg GdWjH Hf YeQ ePgH GdSda aj CSeGA Gddg hUaGJg, heSei GdEjeGf, haj bVGjG egeI aj GdJhMjO, eY JhVjMg deYfi GdSda hGdSdajI, hGdQO Ydi GdaQb GdJj GfMQaJ Yf ePgH GdSda, ShGA cGf GfMQGagG bdjdG Ce cKjQG, ceG hVM aVjdJg Cf GdejRGf GdMbjbj, dhRf GdCehQ GdTQYjI hGdYbOjI gh GdcJGH hGdSfI, hHjf Cf GdcdGe hGdadSaI dG NjQ ajgeG, hCf GdTQjYI ZfjI YfgeG, hHjf efTC GdNWC hGdGfMQGa aj GdCeI, cd Pdc HCSdhH Sgd hGVM, hHYHGQGJ LjOI dG TWW ajgG, ceG Cfg CfUa GdeNGdajf aj CZdH YHGQGJg, hQO Ydjge HCSdhH JhNi ajg GdefgLjI hGdehVhYjI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3OaY eWGYfs -- (3YbjOI s; (3Yde GdcdGes